Response Surface Methodology Based Process Optimization for Biodiesel Production using Cottonseed Oil: A Comparative Study - Waseem Mumtaz, Muhammad; Adnan, Ahmed; Mukhtar, Hamid; Anwar, Farooq; Ahmad, Zahoor; Ashraf Qureshi, Fahim (Asian Journal of Chemistry, 2011)
Present study describes the optimization and comparison of biodiesel production using cottonseed oil as feedstock and NaOH, KOH and NaOCH3 as catalyst to catalyze transesterification of cottonseed oil. Maximum cottonseed oil fatty acid methyl esters (CSOFAME's) yield (%) obtained using NaOCH3, KOH and NaOH was 95.41, 94.25 and 91.4 %, respectively. NaOCH3 was found to be most productive gives best results. GC-MS analysis of CSOFAME's was carried out for compositional analysis. Further fuel properties of CSOFAME's were found compatible with the standards.